VAT Compliance, Trade, and Institutions - Peter Morrow; Michael Smart; Artur Swistak (Center for Economic Studies and ifo Institute (CESifo), 2019)
We develop a simple structural model of value added tax (VAT) compliance, and estimate it using widely available national accounts data to learn about compliance in countries where little is currently known. International border controls improve VAT compliance, generating a correlation between imports and aggregate VAT revenues that is informative about domestic non-compliance. Estimates suggest that revenue lost due to domestic non-compliance is large, particularly in countries with low perceived institutional quality. Border controls keep overall VAT revenues high especially in countries open to international trade.
Keywords: H25; H26; 330